Alone in the face of danger (Journal of Parents and Teachers, 2025)
The article is based on the story of the protagonist, Pepe, who realizes he is alone in the face of the dangers posed by his mother and his aunt Marta. Pepe is in his adolescence, and since his sister is away on a trip, he decides to start writing a diary about his home experiences. Through this introduction, a series of books are presented to help children understand the importance of family, parents, siblings, and the responsibilities that each person has
Keywords: siblings; story; family; diary